Novel multifunctional of magnesium ions (Mg++) incorporated calcium phosphate nanostructures - Thanigai Arul, K.; Ramesh, M.; Chennakesavan, C.; Karthikeyan, V.; Manikandan, E.; Umar, A.; Maaza, M.; Henini, M. (Elsevier, 2018)
Magnesium ions incorporated calcium phosphate was synthesized by wet chemical route and followed by microwave assisted method. XRD analysis was confirmed that the presence of calcium phosphate (hydroxyapatite). TEM analysis was exhibited rod-like morphology. XRF results were showed the percentage of calcium, phosphate, magnesium and oxygen. There was a slight blue shift observed in magnesium ions based samples. Higher magnesium (0.1 Mg-HAp) was revealed the greater discharging time with capacitance voltage (0.55 V). Magnesium based calcium phosphate was showed prolonged rate of drug release. At higher frequency, the Nyquist plot was showed the electrochemical behavior, however at lower frequency, revealed mass transfer process. Magnesium ions tailor the specific capacitance of calcium phosphate. Therefore, magnesium ions based phosphate samples could be an outstanding multifunctional candidate for drug release and supercapacitor applications.